Consecuencias de no incluir una definición legal de obligación en el código civil peruano de 1984 - Vásquez Villacorta, María Isabel (2024)
This degree work was developed in the city of Iquitos, the objective was to analyze the legal, social and lexicographic consequences or effects on law students, legal operators and ordinary people, given the non-inclusion of a legal definition of civil obligation in the Peruvian Civil Code of 1984. This is because the Peruvian Civil Code of 1984 does not contain a definition of civil obligation, its study, conceptualization and understanding, forcing people to resort to doctrinal or jurisprudential interpretation, the same which may be divergent or diverse in terms of its essential components. To carry out this work, a documentary study and a field study were developed, highlighting the exhaustive exploration and analysis of specialized literature related to the topic addressed, as well as the thorough review of regulatory and legislative documents from various government agencies and levels. Finally, the study has proven that law students and legal operators cannot provide a clear and unified definition, as in the case of Legal Act, a figure for which we do find its definition in the Civil Code; and, the general population does not know the term but the majority indicated that they consider the Civil Code as an ideal source to know it. This highlights the importance of addressing this gap to ensure a consistent and understandable application of the law.